2020
DOI: 10.3390/s20123356
|View full text |Cite
|
Sign up to set email alerts
|

Optical Methods Based on Ultraviolet, Visible, and Near-Infrared Spectra to Estimate Fat and Protein in Raw Milk: A Review

Abstract: The present manuscript focuses on reviewing the optical techniques proposed to monitor milk quality in dairy farms to increase productivity and reduce costs. As is well known, the quality is linked to the fat and protein concentration; in addition, this issue is crucial to maintaining a healthy herd and preventing illnesses such as mastitis and ketosis. Usually, the quality of the milk is carried out with invasive methods employing chemical reagents that increase the time analysis. As a solution, several spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Our results demonstrate high scattering effect of WM, due to fat globules and proteins (micellar casein) as reported in the literature (Gunter-ward et al, 2018; Ward et al, 2019). There could be a minor scattering effect due to dissolved minerals and sugar (lactose), however it can be ignored because their proportionate size is lesser than the fat and protein components (Gastélum-Barrios et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate high scattering effect of WM, due to fat globules and proteins (micellar casein) as reported in the literature (Gunter-ward et al, 2018; Ward et al, 2019). There could be a minor scattering effect due to dissolved minerals and sugar (lactose), however it can be ignored because their proportionate size is lesser than the fat and protein components (Gastélum-Barrios et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other spectroscopy-coupled PLS-R models, scattering-based techniques achieve good fat content determination results in raw or unhomogenized milk, also represented by their R 2 values and prediction outcomes. 12,40,41 Bogomolov et al investigated PLS-R models for determining the fat content in raw milk standards of various fat droplet sizes using different validation procedures. 4,15,17 Comparable robust models were built; however, more than one factor was needed because of measuring absorbance and using raw milk.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the current study indicated that the light transmittance percentage became zero at the time of lambing and later. Presence of milk fat globule emulsion can interact with light transmission [23][24][25].…”
Section: Discussionmentioning
confidence: 99%